Proceedings of the 28th ACM Joint Meeting on European Software Engineering Conference and Symposium on the Foundations of Softw 2020
DOI: 10.1145/3368089.3409680
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of bots in software development: characteristics and challenges from a practitioner’s perspective

Abstract: Software engineering bots ś automated tools that handle tedious tasks ś are increasingly used by industrial and open source projects to improve developer productivity. Current research in this area is held back by a lack of consensus of what software engineering bots (DevBots) actually are, what characteristics distinguish them from other tools, and what benefits and challenges are associated with DevBot usage. In this paper we report on a mixed-method empirical study of DevBot usage in industrial practice. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 34 publications
2
38
0
Order By: Relevance
“…Two different individuals could disagree on the interpretation of comments as being produced by bots. As a consequence, a more fine-grained classification of (types of) bots would be needed, building further on the work by Erlenhov et al [20] who identified three types of bot personas based on their autonomy, chat interface, and smartness. It would be definitely interesting to explore how the binary classifier we propose can be generalised to detect these different types of bot personas.…”
Section: Discussionmentioning
confidence: 99%
“…Two different individuals could disagree on the interpretation of comments as being produced by bots. As a consequence, a more fine-grained classification of (types of) bots would be needed, building further on the work by Erlenhov et al [20] who identified three types of bot personas based on their autonomy, chat interface, and smartness. It would be definitely interesting to explore how the binary classifier we propose can be generalised to detect these different types of bot personas.…”
Section: Discussionmentioning
confidence: 99%
“…The main driver for the adoption of bots, according to a study by Erlenhov et al [9], is to increase productivity, although this aspect is seen differently by different DevBot users. We already knew from a study by Meyer et al [10] that developers perceive their workday as productive if they could complete tasks without significant interruptions.…”
Section: Related Workmentioning
confidence: 99%
“…We already knew from a study by Meyer et al [10] that developers perceive their workday as productive if they could complete tasks without significant interruptions. Interestingly, all DevBot users in Erlenhov's study had to some extent issues with interruptions or noise produced by bots: "A good bot waits until a developer is ready for feedback" [9].…”
Section: Related Workmentioning
confidence: 99%
“…Software Bots. Erlenhov et al [9] perform an empirical study about the interaction between practitioners and software bots. They found that there is currently a lack of general-purpose smart bots that go beyond simple automation tools, such as dependency version updating.…”
Section: Related Workmentioning
confidence: 99%